Experimental and numerical study on the flexural performance of reinforced laminated bamboo lumber beams with prestressed GFRP bars - Haitao Li; Dong Yang; Ben Chen; Sarah Mohrmann; Rodolfo Lorenzo; Kun Zhou; Feng Shen (Sustainable Structures)
This paper presents a new method to strengthen laminated bamboo lumber (LBL) beam by embedding prestressed glass fiber reinforced polymer (GFRP) bars at the bottom of LBL beams. The bending test of 30 LBL beams with a size of 2000 mm × 100 mm × 150 mm was carried out with the prestress level and reinforcement ratio as the influencing factors. The test result shows that the failure mode of prestressed LBL beams is mainly the fracture of bamboo fibers at the bottom of the beams. Embedding prestressed GFRP bars in the specimens is a good way to enhance the mechanical properties of LBL beams, including flexural capacity and stiffness. The ultimate bearing capacity of prestressed GFRP bars composited beams are increased to 40.6%, and the bending stiffness are increased by 22.5% comparing with ordinary beams. Based on the test results, a theoretical calculation model for the bearing capacity of the LBL beam was finally proposed, and the calculation results were basically consistent with the experimental results. Finite element modelling (FEM) using continuum damage mechanics was also adopted to verify the failure pattern and the strengthening mechanism of strengthened LBL beams.